Respon Pertumbuhan dan Produksi Beberapa Mutan (M2) Kacang Hijau terhadap Pemberian Air 40% Kapasitas Lapang - Agustina Suryani; Lollie Agustina P. Putri; Mbue Kata Bangun (Jurnal Agroekoteknologi, 2015)
The aims of this research was to evaluate the response of the growth and yield of some mutants (M2) mungbean to water supply of 40% of field capacity. The research was carried out in greenhouse of Agricultural Faculty, University of North Sumatera, Medan, start from December 2013 till March 2014 with eight genotypes, A: is genotype of (F2R0C0), B: is genotype of (M2R1C0),C: is genotype of (M2R1C3), D: is genotype of (M2R2C0), E: is genotype of (M2R2C2), F: is genotype of (M2R3C0), G: is genotype of (M2R3C1), H: is genotype of (M2R3C2), at 40% of Field Capacity by using randomized block design. The treatment was repeated twice. Data were analyzed with ANOVA and continued with LSD. The result of research showed that the mutant genotype B (M2R1C0), E (M2R2C2), and F (M2R3C0) were significantly difference on seed weight per plant, genotype B (M2R1C0) and E (M2R2C2) were significantly difference on 100-seed weight, and genotype E (M2R2C2) was significantly difference on number of pods containingKeywords: Mung bean, mutant (M2), 40% of field capacity.